2019
DOI: 10.4049/jimmunol.1801003
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Antiviral Capacity of T Cell Responses to Adenovirus

Abstract: Adenoviruses are a major cause of infectious mortality in children following allogeneic hematopoietic stem cell transplantation, with adoptive transfer of adenovirus-specific T cells being an effective therapeutic approach. We have previously shown that T cells specific for the peptide epitope LTDLGQNLLY were protective. In this study, we aimed to establish a viral dissemination assay to measure the antiviral capacity of T cells specific for this and other peptide epitopes in an infectious setting. We used rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Beside the verification of the high proliferative capacity of virus-specific T CM in the GMP-product, the PSPA helped us to identify additional antiviral T cell specificities within the T CM compartment. Two AdV epitope-specific CD8 + T cell populations [40,41,63] that had been undetectable in the pre-PSPA T cell screening became visible after stimulation. The frequency of AdV-specific T cells in the peripheral blood is generally low [63] and is dominated by CD4 + T cells as depicted by ICS before PSPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside the verification of the high proliferative capacity of virus-specific T CM in the GMP-product, the PSPA helped us to identify additional antiviral T cell specificities within the T CM compartment. Two AdV epitope-specific CD8 + T cell populations [40,41,63] that had been undetectable in the pre-PSPA T cell screening became visible after stimulation. The frequency of AdV-specific T cells in the peripheral blood is generally low [63] and is dominated by CD4 + T cells as depicted by ICS before PSPA.…”
Section: Discussionmentioning
confidence: 99%
“…Two AdV epitope-specific CD8 + T cell populations [40,41,63] that had been undetectable in the pre-PSPA T cell screening became visible after stimulation. The frequency of AdV-specific T cells in the peripheral blood is generally low [63] and is dominated by CD4 + T cells as depicted by ICS before PSPA. In this regard, the PSPA could become a valuable diagnostic tool to amplify the sensitivity for rare specificities within the T CM compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The data obtained by these researchers indicate that 32 percent of T-cells specific to the LLDQLIEEV epitope amino acid sequence of the E1A inhibited adenoviral propagation. Their results showed that even low levels of specific T cells can accelerate to control the infection and recommend that the performance of the T-cell response is critical to prevention ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies focus on the relationship between adenovirus pathogenesis and T cells, some comparative studies still show that T cell depletion is related to the mortality of adenovirus-infected hematopoietic cell transplant patients [27,28]. Furthermore, some studies have manifested that adenovirus-specific T cells have a specific antiviral ability against adenovirus [29]. In addition, previous studies have explored the effect of CD8 + T cells on the pathogenesis of mouse adenovirus-1 (MAV-1) by establishing an animal model of lung inflammation induced by MAV-1 [30].…”
Section: Discussionmentioning
confidence: 99%